STANDARDIZATION OF RANDANG MEAT RECIPES IN NAGARI CINGKARIANG BANUHAMPU DISTRICK AGAM REGENCY - muaz ar rozi (Jurnal Pendidikan Tata Boga dan Teknologi, 2021)
This study aims to standardize the recipe for beef randang in Nagari Cingkariang, Banuhampu District, Agam Regency. This type of research uses a combination of qualitative research which includes ingredients, spices, tools and processing methods as well as quantitative research, namely analyzing the quality of meat randang in terms of color, shape, texture, aroma and taste. This research was motivated by the absence of standard recipes used in processing, causing differences in recipes and processing results in each tribe that processed randang in Nagari Cingkariang. The source of qualitative data was obtained from several panelists who know and are experts about randang. Then the meat randang recipe is obtained which includes the main ingredients, spices, tools and processing techniques. While the source of quantitative data was obtained from 5 panelists who were trained and skilled at making randang. The research result of standardization of the meat randang recipe was carried out by means of organoleptic testing on the quality and the results obtained were the shape of the randang square cut, the color of the randang brown black, the aroma of randang spices and spices, the soft texture of randang meat and the savory taste of randang.